STRUCTURAL ANALYSIS OF INTRINSIC ELEMENTS IN THE FILM HOW TO MAKE A MILLION BEFORE GRANDMA DIES - Enzy Abdad Subardja; Nadya Fatikhur Rifqi; Safira Azahra Saragih; Fathimah Zahra; Talitha Aulia (CV. RADJA PUBLIKA, 2024)
The film